DNA Mismatch Repair Status Predicts Need for Future Colorectal Surgery for Metachronous Neoplasms in Young Individuals Undergoing Colorectal Cancer Resection. Issue 7 (July 2015) - Aronson, Melyssa; Holter, Spring; Semotiuk, Kara; Winter, Laura; Pollett, Aaron; Gallinger, Steven; Cohen, Zane; Gryfe, Robert
Abstract : BACKGROUND: The treatment of colorectal cancer in young patients involves both management of the incident cancer and consideration of the possibility of Lynch syndrome and the development of metachronous colorectal cancers. OBJECTIVE: This study aims to assess the prognostic role of DNA mismatch repair deficiency and extended colorectal resection for metachronous colorectal neoplasia risk in young patients with colorectal cancer. DESIGN, SETTING, AND PATIENTS: This is a retrospective review of 285 patients identified in our GI cancer registry with colorectal cancer diagnosed at 35 years or younger in the absence of polyposis. MAIN OUTCOME MEASURES: Using univariate and multivariate analysis, we assessed the prognostic role of mismatch repair deficiency and standard clinicopathologic characteristics, including the extent of resection, on the rate of developing metachronous colorectal neoplasia requiring resection. RESULTS: Mismatch repair deficiency was identified in biospecimens from 44% of patients and was significantly associated with an increased risk for metachronous colorectal neoplasia requiring resection (10-year cumulative risk, 13.5% ± 4.2%) compared with 56% of patients with mismatch repair-intact colorectal cancer (10-year cumulative risk, 5.8% ± 3.3%; p = 0.011). In multivariate analysis, mismatch repair deficiency was associated with a HR of 3.65 (95% CI, 1.44–9.21; p = 0.006) for metachronous colorectal neoplasia, whereas extended resection with ileorectal or ileosigmoid anastomosis significantly decreased the risk of metachronous colorectal neoplasia (HR, 0.21; 95% CI, 0.05–0.90; p = 0.036). LIMITATIONS: This study had a retrospective design, and, therefore, recommendations for colorectal cancer surgery and screening were not fully standardized. Quality of life after colorectal cancer surgery was not assessed. CONCLUSIONS: Young patients with colorectal cancer with molecular hallmarks of Lynch syndrome were at significantly higher risk for the development of subsequent colorectal neoplasia. This risk was significantly reduced in those who underwent extended resection compared with segmental resection.